Laser-Deposited In Situ TiC-Reinforced Nickel Matrix Composites: 3D Microstructure and Tribological Properties - Borkar, Tushar; Sosa, John; Hwang, Jun Yeon; Scharf, Thomas W.; Tiley, Jaimie; Fraser, Hamish; Banerjee, Rajarshi (SPRINGER, 2014)
A new class of Ni-Ti-C-based metal-matrix composites has been developed using the laser-engineered net shaping (TM) process. These composites consist of an in situ formed and homogeneously distributed titanium carbide (TiC) phase reinforcing the nickel matrix. Additionally, by tailoring the Ti/C ratio in these composites, an additional graphitic phase can also be engineered into the microstructure. Serial-sectioning, followed by three-dimensional reconstruction of the microstructure in these composites, reveals homogeneously distributed primary and eutectic titanium carbide precipitates as well as a graphitic phase encompassing the primary carbides within the nickel matrix. The morphology and spatial distribution of these phases in three dimensions reveals that the eutectic carbides form a network linked by primary carbides or graphitic nodules at the nodes, which suggests interesting insights into the sequence of phase evolution. These three-phase Ni-TiC-C composites exhibit excellent tribological properties, in terms of an extremely low coefficient of friction while maintaining a relatively high hardness.